(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2023)
The Grăunceanu site in the Olteţ River Valley has yielded a rich carnivoran assemblage including at least 10, possibly 11 species: Vulpes alopecoides, Nyctereutes megamastoides, Ursus etruscus, Meles thorali, Lutraeximia sp., Pliocrocuta perrieri, Lynx issiodorensis, Puma pardoides, Megantereon cultridens, Homotherium latidens and possibly Pachycrocuta brevirostris. The faunal assemblage is compared with approximately coeval sites Europe and western Asia. This comparative analysis shows that the Grăunceanu assemblage shows the greatest similarities with sites to the west such as Senèze and, particularly, Saint-Vallier, rather than more easternly ones such as Liventsovka and Dmanisi. The relative abundance of the taxa at Grăunceanu was compared to that of Saint-Vallier and broad similarities were found, except for the absence of some cursorially adapted taxa present at Saint-Vallier but absent from Grăunceanu. The absence at Grăunceanu of taxa with a reconstructed cursorial hunting strategy, such as Chasmaporthetes and Acinonyx, may suggest less open habitat at Grăunceanu than indicated in previous paleoenvironmental reconstructions.